Evaluation of an FFQ to assess total energy and nutrient intakes in severely obese pregnant women. - Mohd Shukri, Nor Azwani; Bolton, Jennifer L.; Norman, Jane E.; Walker, Brain R.; Reynolds, Rebecca M. (Cambridge Univ Press, 2013)
Objective FFQ are popular instruments for assessing dietary intakes in epidemiological studies but have not been validated for use in severely obese pregnancy. The aim of the present study was to compare nutrient intakes assessed by an FFQ with those obtained from a food diary among severely obese pregnant women. Design Comparison of an FFQ containing 170 food items and a food diary for 4 d (three weekdays and one weekend day); absolute agreement was assessed using the paired t test and relative agreement by Pearson/Spearman correlation, cross-classification into tertiles and weighted kappa values. Setting Antenatal metabolic clinic for severely obese women. Subjects Thirty-one severely obese (BMI at booking ≥40·0 kg/m2) and thirty-two lean control (BMI = 20·0-24·9 kg/m2) pregnant women. Results The findings showed that nutrient intakes estimated by the FFQ were significantly higher than those from the food diary; average correlation was 0·32 in obese and 0·43 in lean women. A mean of 48·5 % of obese and 47·3 % of lean women were correctly classified, while 12·9 % (obese) and 10·0 % (lean) were grossly misclassified. Weighted κ values ranged from -0·04 to 0·79 in obese women and from 0·16 to 0·78 in lean women. Conclusions Overall, the relative agreement between the FFQ and food diary was lower in the obese group than in the lean group, but was comparable with earlier studies conducted in pregnant women. The validity assessments suggest that the FFQ is a useful tool for ranking severely obese pregnant women according to the levels of their dietary intake